Analisis Yuridis terhadap Tindak Pidana Perzinahan yang Dilakukan oleh Menantu terhadap Mertua (Studi Kasus Putusan Nomor 130/Pid.B/2024/Pn Srg) - Uswatun Hasanah (Jurnal Hukum Lex Generalis, 2025)
Adultery is one form of offense against morality as specified in the Indonesian Criminal Law (KUHP). Cases of adultery involving a son-in-law and mother-in- law (or vice versa) raise complex legal issues, not is only from a criminal law perspective but also from social and moral standpoints. Such cases become more complicated when familial values are at stake. This investigation aims to provide a juridical analysis of the crime of adultery committed by a son-in-law against his mother-in-law, by examining Court Decision Number 130/Pid.B/2024/PN Srg. The investigation concentrates on scholarly exploration. The methodological framework utilized adheres to established legal principles, utilizing a case study method. This methodology allows the author to examine the relevant legal provisions and evaluate their significance in particular instances. The research findings indicate that the elements of the unlawful offense of infidelity, as defined in Article 284 In the present situation, the requirements specified within the legal framework of the Penal Code have been sufficiently addressed and met. particularly concerning, the relationship status of the offender and the existence of an affected individual. The assessment of evidence and witness testimony strengthened the judge's conviction in rendering the decision. The court’s ruling illustrates the judge's considerations in applying relevant legal provisions, and highlight the significance of proof and grievances in the legal pursuit process. Adultery is classified as an offense that requires a formal complaint (delik aduan), which means legal proceedings cannot commence without a report from an authorized party. In conclusion, this instance illustrates the significance of a comprehensive grasp of both the subjective and objective elements in the crime of adultery. Furthermore, the increasing complexity of morality-related cases highlights the need for legal reform to better respond to evolving societal values and structures.